Analysis of the Drug Management System at the Pharmacy Installation in the Hospital: a Literature Review - Muji Mulyati; Henry Setyawan; Martini Martini (Universitas Malahayati Lampung, 2023)
ABSTRACT The hospital is an individual health service facility as well as part of the health resources that are very much needed to support the implementation of health efforts. Hospitals must change the paradigm of hospital management towards a consumer perspective, employee empowerment and service quality improvement. One of the efforts to improve the quality of hospital health services can be done by paying attention to the drug management system in pharmaceutical installations. Drug management in hospitals is an important aspect of hospital management to support quality hospital services. This study aims to determine the drug management system in hospital pharmacy installations in Indonesia. This research is a literature review by searching electronic databases published 2017-2022 and meeting the inclusion criteria. Articles were taken from Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight databases with a total of 18 articles used. Based on the review of the journal, the results of eighteen articles showed that there were still deficiencies in the drug management system (planning, procurement, budgeting, storage and distribution) at pharmaceutical installations in hospitals and a solution had to be found immediately to improve the drug management system. Keywords: Pharmaceutical Installations, Drug Management System, Pharmaceutical Services